Graffiti in times of the Covid-19 pandemic: a Folkcommunication based analysis of urban art (Revista Internacional de Folkcomunicação, 2021)
With the year 2020 being marked in History by the worldwide pandemic caused by the new coronavirus and the Covid-19 disease, all traces of human sociability were impacted, not only from the perspective of social isolation, but from the effects of disease and death. Given this commotion, our proposal is to analyze how the various themes of the pandemic were approached from the alternative non-hegemonic and popular communication system, specifically urban graffiti. As a premise, we consider that this form of image expression consists of a channel of Folkcommunication, through which the marginalized layers of society apply a new meaning to “official” communication flows and messages. From image analysis applied to urban graffiti pandemic themed around the world, we explore the capacity of this type of expression to serve as a communicational tool on individual, collective and political levels, acting both in conjunction with the hegemonic discourse in relation to the preventive actions, as in a contesting way, claiming the needs of the popular classes and questioning from a political point of view the actions of national leaders in the pandemic management.